Liver stiffness assessed by Fibrosis-4 index predicts heart failure in AMI patients. (4th February 2022) - Nunohiro, T; Furukawa, K; Uchida, M; Kuwasaki, S; Kusumoto, S; Furudono, S; Suenaga, H; Takeno, M; Takeshita, S
Abstract: Funding Acknowledgements: Type of funding sources: None. It has been recently reported that the liver stiffness, which reflects increased central venous pressure, measured by transient elastography increases along with decompensated heart failure (HF) developing and decreases with clinical improvement. A simple index for the assessment of liver stiffness and/or impairment of liver reserve may be useful in patients with HF. We calculated each patient´s FIB4 index(F4I) using the following formula: (age (years)× aspartate aminotransferase (IU/L)/platelet count (10９/L)× square root of alanine aminotransferase (IU/L)). Patients with an F4I≥2.67 were classified into the high F4I group and these patients were strongly suspected to have non-alcoholic fatty liver disease (NAFLD). NAFLD is also said to be a form of metabolic syndrome expressed in the liver. And lately NAFLD is associated with increased risk of acute myocardial infarction (AMI) and stroke and cardiovascular surrogate markers. But Little is known about F4I with the influence of AMI prognosis. This study included 167 AMI patients who underwent primary percutaneous coronary intervention within 24h of onset. Consecutive patients were divided into two groups based on their F4I at discharge: First group (2.67 ≤F4I, n = 27), second group (F4I <2.67, n = 140) . And we assessed the association between F4I and CV events including cardiac death, recurrent AMI, recurrent PCI (TLR) and re-hospitalization of heart failure during 13 months. Result: High F4I (2.67≤ F4I, 19% VS F4I <2.67, 6%: P = 0.045) related to the re-hospitalization of heart failure. Univariate odds ratio was 3.45. F4I is significantly related to the re-hospitalization of heart failure. Conclusion: A simple index F4I is significantly related to the prognosis of adverse cardiac events after AMI patients.